Collaborative-Consultation: A Pathway for Transition. (Kairaranga, 2014)
Resource Teachers: Learning and Behaviour (RTLB) are specialised teachers who work in regular schools to help facilitate the presence, participation and learning of students who experience difficulties with learning and behaviour. In focusing upon the RTLB principle of a ‘collaborative and seamless model of service’ (Ministry of Education, 2012a), this article examines the theory and evidence that underpins this principle, drawing upon research from overseas and New Zealand. In order to critique the RTLB principle of collaborative consultation in practice, a project undertaken by the authors involving the transition of students from two special classes to a mainstream context is discussed. This discussion reflects on the importance of RTLB working in a collaborative consultation model with school management and staff, the students, parents/whanau and the Ministry of Education, Special Education (MOE:SE) in order to enable positive outcomes for all those involved.